Electronic structure of a new layered bismuth oxyselenide superconductor: LaO0.5F0.5BiSe2. (23rd June 2015) - Xia, M; Jiang, J; Niu, X H; Liu, J Z; Wen, C H P; Lu, H Y; Lou, X; Pu, Y J; Huang, Z C; Zhu, Xiyu; Wen, H H; Xie, B P; et al.
Abstract: LaO F BiSe2 is a new layered superconductor discovered recently, which shows the superconducting transition temperature of 3.5 K. With angle-resolved photoemission spectroscopy, we study the electronic structure of LaO F BiSe2 comprehensively. Two electron-like bands are located around the point of the Brillouin zone, and the outer pockets connect with each other and form large Fermi surface around and . These bands show negligible dispersion, indicating their two-dimensional nature. Based on the Luttinger theorem, the carrier concentration is about 0.53 e per unit cell, close to its nominal value. Moreover, the photoemission data and the band structure calculations agree very well, and the renormalization factor is nearly 1.0, indicating the electron correlations in this material are rather weak. Our results suggest that LaO F BiSe2 is a conventional BCS superconductor without strong electron correlations.